Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The reality of the application of leaders and supervisors in public and private primary schools in Jeddah to indicators of learning outcomes in the light of the supervisory performance leadership system in Saudi schoolsMrs. Sulafah Salah Bajabir , Prof. Najat Mohammed Saeed Alsaigh2. The Interactive Role of Emotional Intelligence in the Relationship between Positive Leadership Behaviors and Job Involvement: An Analytical Study of the Opinions of Academic Leaders in Saudi UniversitiesCo-Prof. Tawfeeq Zayed Mohammad Alregeb3. The effect of teaching using electronic visual notation in developing the skills of jurisprudence of inheritance among secondary school studentsMrs. Huda Muhsiny Altalhi , Prof. Abdullah Mohamad Ayed Al Tameem4. Obstacles to using authentic evaluation strategies in teaching natural sciences from the point of view of science teachers in the both primary and intermediate stages in the city of Makkah Al-MukarramahMr. Mukhlid Saad Al-Otaibi5. Mind- wandering and its Relationship to Academic Engagement among Umm Al- Qura University StudentsMrs. Taghreed Daefallah Al- Huthale , Co- Prof. Nawar Mohammad Saad Al- Harbi6. Emotional Creativity and its relationship to Cognitive Representation and Locus of Control among Talented and Untalented High School female students in Makkah Al-MukarramahMrs. Haneen Ibrahim Alsubhi7. Psychological burnout and its relationship to family adjustment among mothers of children with autism in centers for people with special needs in KhartoumMrs. Sarah Mohamed Ahmed Al- Kashef
Keywords: Journal of Educational and Psychological Sciences